The Phenomenon of Waiting to Know: The lived experience of adults exposed and tested for SARS-CoV-2 - Joana Mariz Pananganan; Laurence Garcia; Michelle Mae Olvido (Asia Pacific Journal of Health Management)
Objective: The study explored the lived experience of adults exposed and tested for SARS-CoV-2 while waiting for their test results.